Evangelicalism and Fundamentalism in the United Kingdom during the Twentieth Century. Edited by David Bebbington and David Ceri Jones - Gould, Graham (The journal of theological studies, 2014)
This collection of 18 essays, plus an editorial introduction and conclusion, is certain to become required reading for anyone interested in twentieth-century evangelical Protestant Christianity in the United Kingdom, or in the problems facing the scholar who tries to define ‘fundamentalism’. It derives from a series of meetings held in 2008 and 2009, funded by a joint AHRC/ESRC grant and by the Evangelical Alliance. The contributions cover a wide range of subjects with some, though minimal, overlap.